Sizing agent for inorganic fibers, inorganic fibers, their manufacturing method, and composite materials

The sizing agent for inorganic fibers, containing cellulose nanofibers and a resin, addresses the adhesion and handling issues of existing sizing agents by enhancing the adhesion of inorganic fibers to the base material and improving the composite material's strength and reliability.

JP7653139B2Active Publication Date: 2025-03-28TAKEMOTO OIL & FAT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021097769
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-11
Publication Date
2025-03-28
Estimated Expiration
2041-06-11

AI Technical Summary

Technical Problem

Existing sizing agents for inorganic fibers, such as those disclosed in Patent Document 1, are insufficient in promoting adhesion between inorganic fibers and base materials, leading to issues with fiber detachment and handling properties.

Method used

A sizing agent for inorganic fibers is developed, containing a specific amount of cellulose nanofibers and a resin, with the cellulose nanofiber content in the nonvolatile portion ranging from 10 ppm to less than 50,000 ppm. This sizing agent is applied to inorganic fibers used in composite materials with a matrix resin, improving adhesion and handling properties.

Benefits of technology

The proposed sizing agent significantly enhances the adhesion of inorganic fibers to the base material, reduces the risk of fiber detachment, and improves handling properties, thereby creating a stronger and more reliable composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653139000006
    Figure 0007653139000006
  • Figure 0007653139000001
    Figure 0007653139000001
  • Figure 0007653139000002
    Figure 0007653139000002
Patent Text Reader

Abstract

To provide a sizing agent for an inorganic fiber which can improve adhesion of an inorganic fiber to a base material, slip-off prevention property and handling property, an inorganic fiber, a method for producing the same, and a composite material.SOLUTION: A sizing agent for an inorganic fiber containing a resin and a cellulose nanofiber is provided, wherein a content ratio of the cellulose nanofiber in a non-volatile content of the sizing agent for the inorganic fiber is 10 ppm or more and less than 50,000. An inorganic fiber is provided, which is attached with the sizing agent for the inorganic fiber. A method for producing an inorganic fiber is provided, which includes a step of attaching the sizing agent for the inorganic fiber to an inorganic fiber. A composite material is provided, which includes the inorganic fiber and a matrix resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sizing agent for inorganic fibers containing cellulose nanofibers, inorganic fibers, a production method thereof, and a composite material. [Background technology]

[0002] In general, fiber-reinforced thermoplastic resin composite materials are known as materials containing inorganic fibers such as carbon fibers and matrix resins such as thermoplastic resins as a base material, and are widely used in various fields such as building materials and transportation equipment. In order to improve the adhesiveness at the interface between the inorganic fibers such as carbon fibers and the base material such as thermoplastic resin, a treatment is carried out in which a sizing agent is attached to the inorganic fibers.

[0003] Conventionally, there have been known sizing agents for inorganic fibers used to reinforce thermoplastic matrix resins, as disclosed in, for example, Patent Document 1. Patent Document 1 discloses sizing-agent-coated carbon fibers in which a sizing agent containing nanocellulose having a number average fiber diameter of 1 to 1000 nm and a compound having an epoxy group is coated on carbon fibers. It is described that the nanocellulose in the sizing agent is contained in an amount of 5 mass% or more based on the total amount of the sizing agent. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-119936 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the sizing agent of Patent Document 1 has a problem in that it does not sufficiently achieve both the adhesiveness of the inorganic fibers to the base material, the ability to prevent falling off, and the handleability. [Means for solving the problem]

[0006] As a result of research aimed at solving the above problems, the present inventors have found that a sizing agent for inorganic fibers containing a specified amount of cellulose nanofibers and a resin is properly and preferably used.

[0007] In order to solve the above problems, one aspect of the present invention is a sizing agent for inorganic fibers that contains a resin and a cellulose nanofiber, wherein the content of the cellulose nanofiber in the non-volatile matter of the sizing agent is 10 ppm or more and less than 50,000 ppm. The resin contains at least one selected from the group consisting of epoxy resin, vinyl ester resin, polyamide resin, polyolefin resin, polyurethane resin, polyester resin, phenoxy resin, polyimide resin, and polyimide resin precursor, and is applied to inorganic fibers used in composite materials using a matrix resin. The gist of this is as follows.

[0008] In the sizing agent for inorganic fibers, the cellulose nanofibers may have a fiber diameter of 1 nm or more and 1000 nm or less. 。

[0009] The sizing agent for inorganic fibers may further contain a surfactant. The sizing agent for inorganic fibers may be applied to glass fibers or carbon fibers. The sizing agent for inorganic fibers may be applied to a composite material in which the resin contains at least one selected from an epoxy resin and a polyester resin, and a matrix resin is an epoxy resin.

[0010] The sizing agent for inorganic fibers may be applied to a composite material in which the resin contains at least one selected from a polyamide resin, a polyurethane resin, a polyimide resin, and a polyimide resin precursor, and a matrix resin is a polyamide resin.

[0011] The sizing agent for inorganic fibers may be applied to a composite material in which the resin contains a vinyl ester resin and a matrix resin is a vinyl ester resin. The sizing agent for inorganic fibers may be applied to a composite material in which the resin contains at least one selected from a polyolefin resin and a phenoxy resin, and a matrix resin is a polyolefin resin.

[0012] In order to solve the above problems, in another aspect of the present invention, the inorganic fiber has a sizing agent attached thereto. It is applied to composite materials using matrix resins. The gist of this is as follows. In order to solve the above problems, in another aspect of the present invention, a method for producing inorganic fibers comprises the steps of: , applied to composite materials using matrix resins The method includes a step of attaching the inorganic fiber to the inorganic fiber.

[0013] In order to solve the above problems, a composite material of another embodiment of the present invention is a composite material comprising the inorganic fibers and a matrix resin, wherein a resin in the sizing agent for the inorganic fibers comprises at least one selected from an epoxy resin and a polyester resin, and the matrix resin is an epoxy resin.

[0014] In order to solve the above problems, a composite material according to another embodiment of the present invention is a composite material comprising the inorganic fibers and a matrix resin, wherein a resin in the sizing agent for the inorganic fibers comprises at least one selected from a polyamide resin, a polyurethane resin, a polyimide resin, and a polyimide resin precursor, and the matrix resin is a polyamide resin.

[0015] In order to solve the above problems, a composite material according to another embodiment of the present invention is a composite material comprising the inorganic fibers and a matrix resin, wherein a resin in the sizing agent for the inorganic fibers comprises a vinyl ester resin, and the matrix resin is a vinyl ester resin.

[0016] In order to solve the above problems, another embodiment of the composite material of the present invention is a composite material comprising the inorganic fibers and a matrix resin, wherein a resin in the sizing agent for the inorganic fibers comprises at least one selected from a polyolefin resin and a phenoxy resin, and the matrix resin is a polyolefin resin. Effect of the Invention

[0017] According to the present invention, it is possible to improve the adhesiveness, the ability to prevent the inorganic fibers from falling off, and the handleability of the inorganic fibers with respect to the base material. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic diagram of an apparatus for evaluating the interface properties of composite materials used to evaluate adhesion in the Examples section. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] First Embodiment First, a first embodiment of a sizing agent for inorganic fibers (hereinafter, also referred to as a sizing agent) according to the present invention will be described. The sizing agent contains a predetermined amount of cellulose nanofibers and a resin.

[0020] (Cellulose nanofiber) The cellulose nanofibers can improve the adhesion between the inorganic fibers and the matrix resin. The cellulose nanofibers are divided into cellulose microfibrils (single cellulose nanofibers) with a basic fiber diameter of 3 to 4 nm, cellulose microfibril bundles with a width of 10 to 20 nm, and microfibrillated cellulose in which the microfibril bundles are further bundled to form a spider web-like network with a width of tens to hundreds of nm, depending on the size, and any of them may be applied. The cellulose nanofibers may be obtained by defibrating and refining plant fiber materials such as wood pulp by a known manufacturing method, or a commercially available product may be applied. The known manufacturing methods are not particularly limited, and examples thereof include a method of crushing with a machine such as a high-pressure homogenizer method or an ultrasonic defibration method, a method of pulverizing with an enzyme such as cellulase, and the like.

[0021] The lower limit of the fiber diameter of the cellulose nanofiber is preferably 1 nm or more, more preferably 3 nm or more. The upper limit of the fiber diameter of the cellulose nanofiber is preferably 1000 nm or less, preferably 800 nm or less. By specifying the fiber diameter within this range, the adhesion between the inorganic fiber and the matrix resin can be improved. In addition, the dispersibility when prepared in a solution can be improved. The fiber diameter of the cellulose nanofiber was measured using a scanning electron microscope (SEM). First, an aqueous dispersion of cellulose nanofiber was dried at 105 ° C for 2 hours and enlarged to a magnification at which the fiber diameter as the fiber width can be measured using an SEM. Twenty non-overlapping cellulose nanofibers were randomly selected, and their fiber diameters were determined. The maximum and minimum values ​​of the fiber diameters obtained are expressed as "fiber diameter (minimum-maximum)" for the cellulose nanofibers. In addition, the average value of the fiber diameters obtained is expressed as "fiber diameter (average value)" for the cellulose nanofibers. In addition, when the cellulose nanofibers are in the form of powder, they were dispersed in water once and used as a homogenized product.

[0022] The sizing agent preferably contains cellulose nanofibers having a fiber diameter of 1 nm or more and 1000 nm or less, more preferably contains 50% or more by mass of the total cellulose nanofibers, and even more preferably contains 80% or more by mass.

[0023] These cellulose nanofibers may be used as one type of cellulose nanofiber alone, or as a combination of two or more types of cellulose nanofibers. The lower limit of the content of cellulose nanofibers in the non-volatile content of the sizing agent is 10 ppm or more, preferably 15 ppm or more. When the content is 10 ppm or more, the adhesion between the matrix resin and the inorganic fiber can be improved. The upper limit of the content is less than 50,000 ppm, preferably 46,000 ppm or less. When the content is less than 50,000 ppm, the handleability can be improved. The non-volatile content is determined from the mass of the bone dry matter obtained by heat-treating the object at 105°C for 2 hours to thoroughly remove volatile substances (hereinafter the same).

[0024] (resin) The resin is appropriately selected from known resins depending on the use of the inorganic fibers to which the sizing agent is applied, etc. Specific examples of the resin include epoxy resin, vinyl ester resin, polyamide resin, polyolefin resin, polyurethane resin, polycarbonate resin, polyester resin, PEEK resin, fluororesin, phenoxy resin, phenol resin, BMI resin, polyimide resin, polyimide resin precursor, polyethersulfone resin, etc. In the present invention, Among these, epoxy resins, vinyl ester resins, polyamide resins, polyolefin resins, polyurethane resins, polyester resins, phenoxy resins, polyimide resins, and polyimide resin precursors are Used .

[0025] Specific examples of the resin include epoxy resin (manufactured by Mitsubishi Chemical Corporation: trade names jER828 and jER1002), epoxy resin (manufactured by Nagase ChemteX Corporation: trade name Denacol EX-521), polyurethane resin (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.: trade name Superflex 500M), modified polypropylene resin (manufactured by Maruyoshi Chemical Co., Ltd.: trade name MGP-1650), modified polypropylene resin (manufactured by Toho Chemical Industry Co., Ltd.: trade name Hi-Tech P-9018), modified polyester resin (manufactured by Toyobo Co., Ltd.: trade name Vylonal MD-1480), phenoxy resin (manufactured by Nippon Steel Chemical & Material Co., Ltd.: trade name YP-50S), polyimide resin precursor of 3,3',4,4'-biphenyltetracarboxylic anhydride and diaminodiphenyl ether, polyamide resin (manufactured by Toray Industries, Inc.: trade name AQ Nylon P-95), polyester resin of ethylene oxide 2 mole adduct of bisphenol A and fumaric acid, and vinyl ester resin of epoxy resin and methacrylic acid.

[0026] Inorganic Fiber is a matrix resin Applied to composite materials 。The type of resin to be blended in the sizing agent is preferably selected in consideration of the type of base material constituting the composite material from the viewpoints of improving adhesion and recyclability. When the matrix resin is applied to an epoxy resin composite material, the resin in the sizing agent is preferably at least one selected from an epoxy resin and a polyester resin. When the matrix resin is applied to a polyamide resin composite material, the resin in the sizing agent is preferably at least one selected from a polyamide resin, a polyurethane resin, a polyimide resin, and a polyimide resin precursor. When the matrix resin is applied to a vinyl ester resin composite material, the resin in the sizing agent is preferably a vinyl ester resin. When the matrix resin is applied to a polyolefin resin composite material, the resin in the sizing agent is preferably at least one selected from a polyolefin resin and a phenoxy resin.

[0027] (Surfactant) The sizing agent may further contain a surfactant. By adding a surfactant, it is possible to improve the ability to prevent the cellulose nanofibers from falling off. Examples of the surfactant include anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants. One type of these surfactants may be used alone, or two or more types of surfactants may be used in combination.

[0028] As the nonionic surfactant, any known surfactant can be appropriately used.Specific examples of nonionic surfactants include (1) compounds in which an alkylene oxide having 2 to 4 carbon atoms is added to an organic acid, an organic alcohol, an organic amine, and / or an organic amide, such as polyoxyethylene dilaurate, polyoxyethylene oleate, polyoxyethylene dioleate, polyoxyethylene octyl ether, polyoxyethylene lauryl ether, polyoxyethylene lauryl ether methyl ether, polyoxyethylene polyoxypropylene lauryl ether, polyoxypropylene lauryl ether methyl ether, polyoxyethylene oleyl ether, polyoxyethylene polyoxypropylene nonyl ether, polyoxyethylene polyoxypropylene octyl ether, an ethylene oxide adduct of 2-hexylhexanol, polyoxyethylene 2-ethyl-1-hexyl ether, polyoxyethylene isononyl ether, polyoxyethylene dodecyl ether, a compound in which ethylene oxide is added to secondary dodecyl alcohol, and polyoxyethylene tridecyl (2) polyoxyalkylene polyhydric alcohol fatty acid ester type nonionic surfactants such as polyoxyalkylene sorbitan trioleate, polyoxyalkylene coconut oil, polyoxyalkylene castor oil, polyoxyalkylene hydrogenated castor oil, polyoxyalkylene hydrogenated castor oil trioctanoate, polyoxyalkylene hydrogenated castor oil maleate, stearic acid ester, or oleic acid ester; (3) alkyl amide type nonionic surfactants such as stearic acid diethanolamide and diethanolamine monolauroamide; (4) polyoxyalkylene fatty acid amide type nonionic surfactants such as polyoxyethylene diethanolamine monooleylamide, polyoxyethylene laurylamine, and polyoxyethylene tallowamine; and (5) ether / ester compounds such as copolymers of polyoxyethylene, dimethyl phthalate, and lauryl alcohol.

[0029] As the anionic surfactant, any known surfactant can be appropriately used. Specific examples of the anionic surfactant include: (1) phosphoric acid ester salts of aliphatic alcohols, such as lauryl phosphate salts, cetyl phosphate salts, octyl phosphate salts, oleyl phosphate salts, and stearyl phosphate salts; (2) phosphoric acid ester salts of aliphatic alcohols to which at least one alkylene oxide selected from ethylene oxide and propylene oxide has been added, such as polyoxyethylene lauryl ether phosphate salts, polyoxyethylene oleyl ether phosphate salts, and polyoxyethylene stearyl ether phosphate salts; (3) aliphatic sulfonates or aromatic sulfonates, such as lauryl sulfonate, myristyl sulfonate, cetyl sulfonate, oleyl sulfonate, stearyl sulfonate, tetradecane sulfonate, dodecyl benzene sulfonate, and secondary alkyl sulfonate (C13-15); (4) sulfate ester salts of aliphatic alcohols, such as lauryl sulfate salts, oleyl sulfate salts, and stearyl sulfate salts; (5) polyoxyethylene lauryl ether sulfate salts, polyoxy Sulfate salts of fatty alcohols to which at least one alkylene oxide selected from ethylene oxide and propylene oxide has been added, such as alkylene (polyoxyethylene, polyoxypropylene) lauryl ether sulfate salts and polyoxyethylene oleyl ether sulfate salts; (6) castor oil fatty acid sulfate salts, sesame oil fatty acid sulfate salts, tall oil fatty acid sulfate salts, soybean oil fatty acid sulfate salts, rapeseed oil fatty acid sulfate salts, palm oil fatty acid sulfate salts, and lard fatty acid sulfate salts (7) sulfate salts of fats and oils such as sulfate salts of castor oil, sulfate salts of sesame oil, sulfate salts of tall oil, sulfate salts of soybean oil, sulfate salts of rapeseed oil, sulfate salts of palm oil, sulfate salts of lard, sulfate salts of beef tallow, and sulfate salts of whale oil; (8) fatty acid salts such as laurates, oleates, and stearates; and (9) sulfosuccinate salts of fatty alcohols such as dioctyl sulfosuccinate.Examples of the counter ion of the anionic surfactant include alkali metal salts such as potassium salts and sodium salts, ammonium salts, and alkanolamine salts such as triethanolamine.

[0030] As the cationic surfactant, known ones can be appropriately used. Specific examples of the cationic surfactant include lauryl trimethyl ammonium chloride, cetyl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, didecyl dimethyl ammonium chloride, 1,2-dimethyl imidazole, and triethanolamine.

[0031] As the amphoteric surfactant, known surfactants can be appropriately used. Specific examples of the amphoteric surfactant include betaine-type amphoteric surfactants. The lower limit of the content of the surfactant in the non-volatile content of the sizing agent is preferably 1% by mass or more, more preferably 2% by mass or more. When the content is 1% by mass or more, the anti-dropping property can be further improved. The upper limit of the content of the surfactant is preferably 50% by mass or less, more preferably 40% by mass or less. When the content is 50% by mass or less, the adhesiveness can be further improved.

[0032] The action and effect of the sizing agent of this embodiment will be described. (1-1) The sizing agent of this embodiment is configured to contain a predetermined amount of cellulose nanofibers and resin. Therefore, it is possible to improve the adhesion of the inorganic fibers to the base material and the resistance to falling off. In particular, the sizing agent is applied directly to the surface of the inorganic fibers, and unevenness derived from the cellulose nanofibers is formed on the fiber surface, so that the adhesion is improved by the anchor effect. In addition, when a matrix resin is applied on the sizing agent, the expansion of cracks at the interface between the inorganic fibers and the matrix resin can be suppressed, and the strength of the composite material can be improved.

[0033] (1-2) The sizing agent is configured so that the content of cellulose nanofibers in the non-volatile content is less than 50,000 ppm. This improves the fluidity of the sizing agent solution or suppresses a decrease in fluidity. In addition, when the sizing agent is diluted with a solvent or when the sizing agent is prepared, the sizing agent can be easily mixed with the solvent. This improves the handleability of the sizing agent.

[0034] <Second embodiment> Next, a second embodiment of the method for producing inorganic fibers according to the present invention will be described. The second embodiment has the same configuration as the first embodiment except for the following description.

[0035] The method for producing inorganic fibers of this embodiment includes the steps of: , inorganic materials applied to composite materials using matrix resins The process includes a step of adhering the sizing agent to the fibers. There is no particular restriction on the amount of the sizing agent attached (excluding the solvent), but it is preferable that the amount of the sizing agent attached to the inorganic fibers be 0.01% by mass or more and 10% by mass or less. By specifying the amount of the sizing agent to be within this range, the effect of the bundling property of the inorganic fibers can be further improved.

[0036] (Inorganic fiber) The type of inorganic fiber applied in this embodiment is not particularly limited, and examples thereof include glass fiber, carbon fiber, ceramic fiber, metal fiber, mineral fiber, rock fiber, slag fiber, etc. Among these, glass fiber and carbon fiber are preferred from the viewpoint of more effectively exerting the effects of the present invention. Examples of the type of carbon fiber include PAN-based carbon fiber obtained from acrylic fiber as a raw material, pitch-based carbon fiber obtained from pitch as a raw material, recycled carbon fiber, polyester fiber, and carbon fiber obtained from polyethylene resin, phenol resin, cellulose resin, lignin resin, etc. as raw materials.

[0037] To apply the sizing agent of the first embodiment to the inorganic fibers, a method generally used industrially can be applied. For example, a roller immersion method, a roller contact method, a spray method, a papermaking method, etc. can be mentioned. The inorganic fibers to which the sizing agent has been applied may be subsequently dried using a known method.

[0038] According to the method for producing inorganic fibers of this embodiment, in addition to the effects of the first embodiment, the following effects can be obtained. (2-1) In the method for producing inorganic fibers according to the present embodiment, a sizing agent containing cellulose nanofibers and a resin is used. inorganic This method includes a process of attaching the sizing agent to the fibers. Therefore, it is possible to improve the prevention of cellulose nanofibers from falling off from inorganic fibers. In addition, since the application of the sizing agent to the inorganic fibers is completed in one process, the process efficiency can also be improved.

[0039] <Third embodiment> Next, a third embodiment of the composite material according to the present invention will be described. The third embodiment has the same configuration as the first and second embodiments, except for the following description.

[0040] A composite material can be obtained by impregnating the inorganic fibers to which the sizing agent is attached in the second embodiment with a matrix resin as a base material. When producing the composite material, the form of the inorganic fibers is not particularly limited, and for example, long fiber, short fiber, nonwoven fabric, etc. can be used.

[0041] (Matrix resin) The matrix resin is appropriately selected from known resins depending on the purpose, use, etc. of the composite material. Specific examples of the matrix resin include epoxy resin, vinyl ester resin, polyamide resin, polyolefin resin, polyurethane resin, polycarbonate resin, polyester resin, PEEK resin, fluororesin, phenoxy resin, phenol resin, BMI resin, polyimide resin, polyimide resin precursor, polyethersulfone resin, etc. Of these, the present invention uses epoxy resins, vinyl ester resins, polyamide resins, polyolefin resins, polyurethane resins, polyester resins, phenoxy resins, polyimide resins, and polyimide resin precursors.

[0042] The matrix resin may be selected in consideration of the type of resin contained in the sizing agent from the viewpoints of improving adhesion, improving recyclability, etc. When the matrix resin is applied to an epoxy resin composite material, the resin in the sizing agent is preferably at least one selected from an epoxy resin and a polyester resin. When the matrix resin is applied to a polyamide resin composite material, the resin in the sizing agent is preferably at least one selected from a polyamide resin, a polyurethane resin, a polyimide resin, and a polyimide resin precursor. When the matrix resin is applied to a vinyl ester resin composite material, the resin in the sizing agent is preferably a vinyl ester resin. When the matrix resin is applied to a polyolefin resin composite material, the resin in the sizing agent is preferably at least one selected from a polyolefin resin and a phenoxy resin.

[0043] According to the composite material of this embodiment, the following effects can be obtained. (3-1) In the composite material of the present embodiment, a sizing agent containing a predetermined amount of cellulose nanofibers and a resin is applied. Therefore, due to the excellent adhesion between the inorganic fibers and the matrix resin, a fiber-reinforced resin composite material having various excellent properties, particularly mechanical properties, can be obtained.

[0044] The above embodiment may be modified as follows: The above embodiment and the following modifications may be combined with each other to the extent that no technical contradiction occurs. The sizing agent of the above embodiment does not preclude the addition of other ingredients such as water or an organic solvent, a smoothing agent, an antioxidant, and a preservative, from the viewpoint of maintaining the performance of the sizing agent and improving the applicability to inorganic fibers, within the scope that does not impair the effects of the present invention.

[0045] The fields to which the sizing agent of the above embodiment is applicable are: Applied to inorganic fibers used in composite materials with matrix resins . Composite materials include: For example, carbon fiber composites (CFRP) impregnated with matrix resin such as polyimide resin. The following are some of the reasons: Other As a reference example , concrete reinforcing fibers, etc. Examples include . EXAMPLES

[0046] In the following, examples will be given to more specifically describe the configuration and effects of the present invention, but the present invention is not limited to these examples. In the following examples and comparative examples, parts means parts by mass, and % means % by mass.

[0047] Test section 1 (preparation of sizing agent) The sizing agent of Example 1 used cellulose nanofibers (A-1) with fiber diameters (minimum-maximum) of 20-300 nm and average fiber diameters of 180 nm shown in Table 1 as raw materials, epoxy resin (B-1) shown in Table 2 as resin (B), and random adduct (C-1) of 30 moles of ethylene oxide and 5 moles of propylene oxide of tristyrenated phenol shown in Table 3 as surfactant (C). A pre-prepared resin emulsion, a pre-prepared aqueous dispersion of cellulose nanofibers, and a surfactant were mixed to obtain an aqueous solution of the sizing agent of Example 1 having the content ratios shown in Table 4.

[0048] The sizing agents of Examples 2 to 15 and Comparative Examples 1 to 5 used as raw materials cellulose nanofibers (A) in Table 1, resins (B) in Table 2, and, if necessary, surfactants (C) in Table 3. The components were mixed in the content ratios shown in Table 4, and aqueous solutions of the sizing agents were obtained by the preparation methods shown in A to E below.

[0049] A: The mixture of each raw material was heated to 100°C and homogenized, then cooled to below 70°C and water was gradually added to obtain an aqueous solution of the sizing agent. B: An aqueous solution of a sizing agent was obtained by mixing a resin emulsion containing a surfactant that had been prepared in advance with an aqueous dispersion of cellulose nanofibers that had been prepared in advance.

[0050] C: An aqueous solution of a sizing agent was obtained by mixing a previously prepared resin emulsion, a previously prepared aqueous dispersion of cellulose nanofibers, and a surfactant. D: An aqueous solution of a sizing agent was obtained by mixing a resin emulsion prepared in advance with an aqueous dispersion of cellulose nanofibers prepared in advance.

[0051] E: An aqueous solution of a sizing agent was obtained using a resin emulsion prepared in advance. The type and content of cellulose nanofiber (A), the type and content as non-volatile matter of resin (B), the type and content of surfactant (C), and the preparation method of the sizing agent are shown in the "Cellulose nanofiber (A)", "Resin (B)", "Surfactant (C)", and "Mixing method during manufacture" columns of Table 4. The non-volatile matter of resin (B) was determined as the mass of the bone-dry matter after heat-treating the subject at 105°C for 2 hours to thoroughly remove volatile substances.

[0052] [Table 1]

[0053] [Table 2]

[0054] [Table 3]

[0055] [Table 4] Details of the matrix resins used in the adhesive property evaluation shown in Table 4, *1) to *3), are as follows.

[0056] (Matrix resin used for adhesiveness evaluation) Epoxy resin (Mitsubishi Chemical Corporation, product name: jER828+triethylenetetramine) Vinyl ester resin (manufactured by Showa Denko Co., Ltd., product name: Lipoxy R-804B (uses Showa Denko Co., Ltd.'s methyl ethyl ketone peroxide hardener)) Polyamide resin (UBE Nylon 1011FB manufactured by Ube Industries) Polypropylene resin: 2% maleic anhydride modified polypropylene *1) Non-volatile content standard *2) Parts by mass per 100 parts by mass of the total of the non-volatile content of resin (B) and surfactant *3) Sizing agent content in non-volatile matter (ppm) Test Category 2 (Evaluation) Adhesion evaluation The adhesiveness was evaluated by measuring the stress by the microdroplet method using a commercially available composite interface characterization device. Figure 1 shows a schematic diagram of the composite interface characterization device 10.

[0057] The aqueous liquid of each example prepared as described above was further diluted with water to prepare an aqueous liquid with a solid content of 2%. This aqueous liquid was applied to a strand of carbon fiber or glass fiber by a dipping method so that the solid content was 2%, thereby preparing a strand of carbon fiber or glass fiber to which the sizing agent of each example was applied.

[0058] Next, one carbon fiber or glass fiber was taken out from the carbon or glass fibers, and both ends of this fiber 12 were fixed in a tensioned state to a plate-like rectangular frame-shaped holder 11 with adhesive 14. Next, the matrix resin of each example shown in Table 4 was attached to the fiber 12 so as to form a resin droplet 13 with a diameter of approximately 70 μm, and fixed.

[0059] Two plate-like blades 17, 18, each having a tapered vertical cross section on one side, are attached to an apparatus main body (not shown) in a position where their tips 17a and 18a face each other.

[0060] The holder 11 was attached to the substrate 16 fixed to the device body at a position where the fiber 12 to which the resin droplet 13 was fixed was sandwiched between the tips 17a, 18a of the two blades 17, 18. A load cell 15 was connected to the substrate 16, and the stress applied to the substrate 16 was measured.

[0061] When the holder 11 was moved in the fiber axial direction at a speed of 5 mm / min, the maximum stress F generated when the resin droplet 13 was peeled off from the fiber 12 by the tips 17a, 18a of the blades 17, 18 was measured by the load cell 15.

[0062] Using the measured values, the interfacial shear strength τ was calculated according to the following equation 1. The same operation was carried out 20 times, and the average interfacial shear strength values ​​obtained were calculated. Furthermore, the increase rate of the average value obtained relative to the reference value of the matrix resin used, shown below, was calculated and evaluated according to the following criteria. The results are shown in "Adhesion" in Table 4. The type of inorganic fiber and the type of matrix resin used are shown in the "Inorganic fiber used in adhesion evaluation" and "Matrix resin used in adhesion evaluation" columns of Table 4, respectively.

[0063]

number

[0064] - Standard value of matrix resin used Epoxy resin: 60MPa Vinyl ester resin: 40MPa Polyamide resin: 50MPa Polypropylene resin: 22MPa ○(Acceptable): Increase rate is 5% or more × (Not acceptable): Increase rate is less than 5% -Evaluation of anti-falling properties After the fibers passed through a sizing bath to apply a sizing agent, the fibers were dried and then evaluated for their ability to prevent the cellulose nanofibers from falling off at the metal rollers according to the following criteria. The results are shown in the "Anti-falling ability" column in Table 4.

[0065] ◎ (Good): No cellulose nanofibers were found to fall off the metal rollers, and continuous operation for more than two weeks was possible. ○ (Acceptable): A small amount of cellulose nanofiber was found to have fallen off the metal roller, but continuous operation for more than two weeks was possible. × (Not acceptable): When there was a large amount of cellulose nanofiber falling off the metal roller and it was necessary to stop production and clean it within two weeks. Handling The handleability of each sizing agent was evaluated according to the following criteria. The results are shown in the "Handleability" column of Table 4.

[0066] ○ (Acceptable): When used as a one-liquid sizing agent in the inorganic fiber manufacturing process, the sizing agent maintained its fluidity, and it was easy to measure its weight and add it to the process using a pump. × (Not acceptable): When used as a one-liquid sizing agent in the inorganic fiber manufacturing process, the sizing agent did not maintain its fluidity, making it difficult to measure its weight and to pump it into the process.

[0067] -Evaluation of process efficiency The process efficiency of each sizing agent was evaluated according to the following criteria. The results are shown in the "Process Efficiency" column of Table 4.

[0068] ○ (OK): When the application of cellulose nanofiber and resin to the fiber is completed in one step × (Not acceptable): When there is a two-step process in which cellulose nanofibers are applied to fibers, and then a sizing agent containing resin is applied to the fibers. As is clear from the results in Table 4, the sizing agents of the respective Examples were evaluated as acceptable or better in terms of adhesion, resistance to shedding, handleability, and process efficiency. The present invention has the effect of improving adhesion, resistance to shedding, handleability, and process efficiency. Next, the technical ideas that can be understood from the above-described embodiment and other examples will be described below. One aspect relates to a sizing agent for inorganic fibers that contains a resin and cellulose nanofibers, and the content of the cellulose nanofibers in the non-volatile matter of the sizing agent is 10 ppm or more and less than 50,000 ppm. In the sizing agent for inorganic fibers, the cellulose nanofibers may have a fiber diameter of 1 nm or more and 1000 nm or less. In the sizing agent for inorganic fibers, the resin may contain at least one selected from an epoxy resin, a vinyl ester resin, a polyamide resin, a polyolefin resin, a polyurethane resin, a polyester resin, a phenoxy resin, a polyimide resin, and a polyimide resin precursor. The sizing agent for inorganic fibers may further contain a surfactant. The sizing agent for inorganic fibers may be applied to glass fibers or carbon fibers. The sizing agent for inorganic fibers may be applied to a composite material in which the resin contains at least one selected from an epoxy resin and a polyester resin, and a matrix resin is an epoxy resin. The sizing agent for inorganic fibers may be applied to a composite material in which the resin contains at least one selected from a polyamide resin, a polyurethane resin, a polyimide resin, and a polyimide resin precursor, and a matrix resin is a polyamide resin. The sizing agent for inorganic fibers may be applied to a composite material in which the resin contains a vinyl ester resin and a matrix resin is a vinyl ester resin. The sizing agent for inorganic fibers may be applied to a composite material in which the resin contains at least one selected from a polyolefin resin and a phenoxy resin, and a matrix resin is a polyolefin resin. In another embodiment, the inorganic fibers have the sizing agent for inorganic fibers attached thereto. In another embodiment, a method for producing inorganic fibers includes a step of adhering the sizing agent for inorganic fibers to inorganic fibers. Another embodiment of the composite material is a composite material including the inorganic fibers and a matrix resin, wherein the resin in the sizing agent for the inorganic fibers includes at least one selected from an epoxy resin and a polyester resin, and the matrix resin is an epoxy resin. Another embodiment of the composite material is a composite material including the inorganic fibers and a matrix resin, wherein the resin in the sizing agent for the inorganic fibers includes at least one selected from a polyamide resin, a polyurethane resin, a polyimide resin, and a polyimide resin precursor, and the matrix resin is a polyamide resin. Another embodiment of the composite material is a composite material including the inorganic fibers and a matrix resin, wherein the resin in the sizing agent for the inorganic fibers includes a vinyl ester resin, and the matrix resin is a vinyl ester resin. Another embodiment of the composite material is a composite material comprising the inorganic fibers and a matrix resin, wherein the resin in the sizing agent for the inorganic fibers comprises at least one selected from a polyolefin resin and a phenoxy resin, and the matrix resin is a polyolefin resin. [Explanation of symbols]

[0069] 10…Composite interface characteristic evaluation device 11…Holder 12…Fiber 13…Resin Droplet 14…Glue 15…Load cell 16...Substrate 17,18…Blade

Claims

1. A sizing agent for inorganic fibers containing a resin and a cellulose nanofiber, wherein a content ratio of the cellulose nanofiber in a non-volatile matter of the sizing agent for inorganic fibers is 10 ppm or more and less than 50,000 ppm; The sizing agent for inorganic fibers is characterized in that the resin contains at least one selected from epoxy resins, vinyl ester resins, polyamide resins, polyolefin resins, polyurethane resins, polyester resins, phenoxy resins, polyimide resins, and polyimide resin precursors, and is applied to inorganic fibers used in composite materials using a matrix resin.

2. The sizing agent for inorganic fibers according to claim 1 , wherein the cellulose nanofibers include those having a fiber diameter of 1 nm or more and 1000 nm or less.

3. The sizing agent for inorganic fibers according to claim 1 or 2, further comprising a surfactant.

4. The sizing agent for inorganic fibers according to any one of claims 1 to 3, which is applied to glass fibers or carbon fibers.

5. The sizing agent for inorganic fibers according to any one of claims 1 to 4, which is applied to a composite material in which the resin contains at least one selected from an epoxy resin and a polyester resin, and a matrix resin is an epoxy resin.

6. The sizing agent for inorganic fibers according to any one of claims 1 to 4, which is applied to a composite material in which the resin contains at least one selected from a polyamide resin, a polyurethane resin, a polyimide resin, and a polyimide resin precursor, and a matrix resin is a polyamide resin.

7. The sizing agent for inorganic fibers according to any one of claims 1 to 4, which is applied to a composite material, wherein the resin contains a vinyl ester resin and a matrix resin is a vinyl ester resin.

8. The sizing agent for inorganic fibers according to any one of claims 1 to 4, which is applied to a composite material in which the resin contains at least one selected from a polyolefin resin and a phenoxy resin, and a matrix resin is a polyolefin resin.

9. 5. An inorganic fiber having the sizing agent for inorganic fibers according to claim 1 attached thereto, the inorganic fiber being used in a composite material using a matrix resin.

10. A method for producing inorganic fibers, comprising a step of adhering the sizing agent for inorganic fibers according to any one of claims 1 to 8 to inorganic fibers to be used in a composite material using a matrix resin.

11. 10. A composite material comprising the inorganic fiber according to claim 9 and a matrix resin, wherein the resin in the sizing agent for the inorganic fiber comprises at least one selected from an epoxy resin and a polyester resin, and the matrix resin is an epoxy resin.

12. 10. A composite material comprising the inorganic fiber according to claim 9 and a matrix resin, wherein the resin in the sizing agent for inorganic fiber contains at least one selected from a polyamide resin, a polyurethane resin, a polyimide resin, and a polyimide resin precursor, and the matrix resin is a polyamide resin.

13. 10. A composite material comprising the inorganic fibers according to claim 9 and a matrix resin, wherein the resin in the sizing agent for the inorganic fibers comprises a vinyl ester resin, and the matrix resin is a vinyl ester resin.

14. A composite material comprising the inorganic fiber according to claim 9 and a matrix resin, wherein the resin in the sizing agent for the inorganic fiber contains at least one selected from a polyolefin resin and a phenoxy resin, and the matrix resin is a polyolefin resin.

Citation Information

Patent Citations

  • Fiber convergence agent

    JP2016079507A

  • Sizing agent coated carbon fiber, manufacturing method of sizing agent coated carbon fiber, prepreg and carbon fiber reinforced composite material

    JP2017119936A

  • Surface coated reinforced fiber, manufacturing method of the surface coated reinforced fiber, intermediate substrate, composite material and molded body containing the surface coated reinforced fiber and resin

    JP2020007650A

  • Cord for rubber reinforcement and rubber product using same

    WO2019159733A1